Unlocking the Success of MSMEs in Digital Era: Shopee Digital Literacy Training, Form SDGs Number 8 - Rahmawati, Apriana; Yanto, Alif Faruqi Febri; Firdaus, Mohammad Iqbal (Society : Jurnal Pengabdian Masyarakat, 2024)
The aim is for MSMEs to understand the role of digital literacy on the Shopee platform. Providing this education is a form of Shopee's support for Sustainable Development Goals (SDGs) number 8, namely "Decent work and inclusive economic growth. This can also strengthen the ability of MSMEs to utilize digital technology to reach more customers, increase sales and develop their business. Supports the creation of new jobs and increases people's income in Gunung Gangsir Village.The method used in this activity is to create a Community Service (PKM) activity by providing counseling regarding the use of online technology (online system) to MSMEs in Gunung Gangsir Village, Pasuruan Regency. Community service activities in Gunung Gangsir Village through Shopee digital literacy education have provided many benefits for the village community. This activity is a real example of how digital technology can be used to improve community welfare and build a more advanced village.